"Don`t touch my bag": The role of superstition in professional male boxing - Allen, G.; Thornton, C.; Riby, H. (The Sport Psychologist, 2020)
The superstitious actions athletes undertake before competition have been well documented, yet the role of such behaviors has received little qualitative attention. The aim of this study was to explore the role of superstitious routines in professional male boxing. A descriptive phenomenological approach was adopted, and individual semistructured interviews were conducted with 5 professional male athletes in the United Kingdom. Results show that superstition is regularly used by boxers in the lead-up to fights to aid mental preparation, fulfill a need for control, and improve the likelihood of success. Common themes emerged, such as the use of praying and engagement in acts thought to bring good luck and/or the avoidance of behaviors that might bring bad luck. Findings also indicate that despite a rational link, boxers use superstition as a coping mechanism (e.g., as a scapegoat/excuse for losing) and to gain a sense of control.